2010
DOI: 10.1259/bjr/14078580
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic myxofibroma synchronous with primary angiosarcoma of the spleen

Abstract: ABSTRACT. Odontogenic myxofibroma of the temporomandibular joint (TMJ) is a rare tumour; moreover, primary splenic angiosarcoma (PAS) in paediatric patients is extremely rare. We report on a 15-year-old boy who presented with right TMJ swelling and subsequently developed epigastric and right upper quadrant pain. The TMJ swelling proved to be odontogenic myxofibroma and the abdominal pain was a result of primary splenic angiosarcoma with hepatic metastasis. We report for the first time the synchronous presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Fifteen articles, reporting in details the experience with 24 patients, were identified and included in the present review ( 1 , 3 , 9 , 10 - 21 ). Two cases (8.3%) were peripheral MFs and 22 (91.7%) were central tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen articles, reporting in details the experience with 24 patients, were identified and included in the present review ( 1 , 3 , 9 , 10 - 21 ). Two cases (8.3%) were peripheral MFs and 22 (91.7%) were central tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The radiographic appearances are reported in Table 2 ( 1 , 3 , 9 , 10 - 21 ). For 10 cases no data on radiology were available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we report a case of high-grade extremity MFS with a synchronous mesenteric LMS. The synchronous development of multiple primary sarcomas of different histopathology is extremely rare [17] and very few cases have been reported in the literature [4,18,19]. In their review of 5505 sarcomas, Grobmyer et al [20] reported only for 2 patients (0.04%) who presented with synchronous soft tissue sarcomas of distinct pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Each cycle of chemotherapy was followed by G-CSF prophylaxis. Radiologic images of the metastatic lesion, both 18 FDG-PET and abdominal CT scans, were taken after the final cycle. The malignant mass in the right lower abdomen had no significant changes in size (5.2 × 5.0 cm) or FDG uptake (SUV max = 15.3) from what was previously noted.…”
Section: Case Historymentioning
confidence: 99%